2011
DOI: 10.1590/s1809-48722011000200003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent Diagnosis of Orofacial Fissures in a Reference Service with Resident Cases in the State of Mato Grosso do Sul

Abstract: Introduction:The orofacial fissures are among the most frequent congenital malformations and show a clinical diversity, causing a series of severe complications permanently observed in the individual through his/her lifetime. Objective:To estimate the prevalent types of congenital orofacial fissures diagnosed in a reference service with resident cases in the State In brief, there were 271 diagnosed cases in the reference service, with the unilateral incisive trans-foramen fissures prevailing for the left side,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 12 publications
2
8
0
8
Order By: Relevance
“…According to epidemiological studies investigating several population samples, CLPs occur more frequently than other types of clefts, such as CL and CP 1,[4][5][6] . The results of the present study corroborate the literature by showing that CLPs are more frequent than CL and CP, with both latter clefts having similar frequencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to epidemiological studies investigating several population samples, CLPs occur more frequently than other types of clefts, such as CL and CP 1,[4][5][6] . The results of the present study corroborate the literature by showing that CLPs are more frequent than CL and CP, with both latter clefts having similar frequencies.…”
Section: Discussionmentioning
confidence: 99%
“…Freitas et al 6 performed a study with a population affected by orofacial clefts in the State of Bahia, and by analysing the medical records, the authors also reported a higher predominance of blacks and mulattos. On the other hand, Gardenal et al 5 conducted a study in the State of Mato Grosso do Sul based on medical records and they identified a higher predominance of Caucasian individuals with cleft palate, followed by blacks and mulattos. Another study conducted by Cuozzo et al 9 in the State of Mato Grosso showed a much higher predominance of white individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Por outro lado, BARONEZA et al (14) e GARDENAL et al (15) observaram também que a fissura transforame era a de maior ocorrência, mas seguida pela fissura pré-forame e depois pela do tipo pós-forame incisivo (14,15).…”
Section: -38%unclassified
“…A fissura pós-forame foi mais prevalente no sexo feminino, representando 62% dos casos, o que é reforçado pelos achados outros estudos (11)(12)(13)(14)(15).…”
Section: -38%unclassified
“…Os grupos de medicamentos mais utilizados foram as vitaminas (79,4%), seguido dos antibióticos (9,1%), anticoncepcionais (2,5%) e anti-hipertensivos (2,5%). (3,(16)(17)(18)(19).…”
Section: Resultsunclassified